Penerapan Model Pembelajaran Bersiklus Untuk Meningkatkan Hasil Belajar Siswa Materi ASEAN - Supriono, Joko (Inovasi: Jurnal Diklat Keagamaan, 2020)
Based on observations made by researchers, the reality that occurs in the field proves that in learningSocial Sciences (IPS) only by the lecture method, this causes the material on social studies subjects to notbe conveyed properly. After the teacher or researcher uses various methods combined with thelearning cycle model in learning, students are expected not to feel bored and the material can be conveyedproperly. Through the learning cycle model, it can be learned a variety of very interesting and funmaterial, such as the ASEAN material. This research is a classroom action research (PTK) which aims todetermine student learning outcomes by using a cycled Learning Model to improve student learningoutcomes on ASEAN material in junior high Negeri 2 Jatirejo Class VIII - C Semester 1 Academic Year2019/2020. This research was conducted in August - September 2019 in class VIII - C involving 31students. The research was carried out for two cycles through a series of activities, namely planning,implementation, observation, and reflection. Based on the results of the research and discussion above itcan be concluded that learning by using a cycled learning model can improve student learning outcomesfrom 87.10 % in the first cycle to 90.32 % in the second cycle. In addition, cycle learning in social studiessubject matter with ASEAN subject matter in SMP Negeri 2 Jatirejo class VIII - C Semester 1 of the 2019/2020 academic year runs more effectively as indicated by the enthusiasm of students which increases inlearning from 86.33 % in the first cycle to 93.53 % in the second cycle, scientific behavior also improvedand in both cycles of good category, and the quality of learning also improved as evidenced by theimplementation of the RPP reached 100 % and the average score of 4.45 (good)